Efficiency analysis of irrigation ditches over different land uses in the Andean region of Ecuador: implication for nature-based water management strategies - Matovelle, Carlos; Mudarra-Martínez, Matías; Andreo-Navarro, Bartolomé (Springer Nature, 2025)
Human pressures and global change are threatening water resources. Circumstances vary in each location; therefore, finding solutions that address local issues helps achieve comprehensive water management strategies. In the Andean basins, the pre-Inca cultures used nature-based water management techniques to deal with the dry seasons. This knowledge and these echniques have been recognized as a strategy to increase water security. Additionally, they have been unconsciously applied to improve hydrological conditions in areas affected by extreme land-use changes. Water sowing and harvesting techniques have been used to manage territories dedicated to livestock and agriculture. This research evaluates three traditional infiltration ditch systems on two types of land use (páramo and cultivated pastures) in the Andean region of Azuay (Ecuador). The objective was to establish the potential for better management of water resources in dry seasons. Eosin-traced water diverted through channels or ditches, infiltrated into the soil, was retained for an average of 31 days in the páramo soil and from 90 to 111 days in the cultivated pasture soil. Controlled water infiltration contributes to effective water management by retaining water in the soil for extended periods. We conclude that nature-based systems perform better on soils with higher water retention capacity. These techniques are suitable for managing water in areas where land changes have reduced water storage potential.
Keywords: Andes (Cuenca hidrográfica); Cuencas hidrográficas - Gestión; Andean basin; Water management; Nature-based solutions; Sustainability